Octagonal Photonic Crystal Fiber Magnetic Field Sensor Based on Surface Plasmon Resonance Effect - Li, Mingliang; Cao, Ying; Li, Jianhua; Li, Zonglin; Zhang, Ru; Meng, Fanchao (Plasmonics (Norwell, Mass.), 2025)
This paper describes an octagonal photonic crystal fiber (OPCF) magnetic field sensor based on the surface plasmon resonance effect. The magnetic fluid is filled into the first layer of air holes of the OPCF, and the Au is coated into the air hole located in the y -direction. The external magnetic field intensity can be determined by observing the change in the confinement loss spectra caused by the effect of the external magnetic field on the refractive index of the magnetic fluid. A finite element method is used to simulate the effects of structural parameters such as air hole diameter, stomatal spacing, and gold coating thickness on the performance of the fiber optic magnetic field sensor. The sensitivity of the proposed optical fiber magnetic field sensor is 757.1 pm/Oe, a FOM value of 2.16 Oe −1 , and an AS value of 1.43 × 10 −3 Oe −1 , and the detection range is 50–200 Oe. The OPCF magnetic field sensor enables the development of lightweight and high-precision electromagnetic detection equipment due to the fact that OPCF magnetic field sensors do not require excessive modification of PCF, have less damage, are simple in structure, and have low production costs. It will improve the efficiency and quality of data collection in electromagnetic geological exploration and accelerate the transformation and upgradation of intelligent and green geological exploration.